Severe Defects in Dorsal Thalamic Development in Low-Density Lipoprotein Receptor-Related Protein-6 Mutants - Zhou, Cheng-Ji (J Neurosci, 2004)
Mice with mutations in the Wnt coreceptor low-density lipoprotein receptor-related protein-6 (LRP6) have a smaller and severely disorganized dorsal thalamus and lack thalamocortical projections. Using molecular markers, we showed that most dorsal thalamic and epithalamic neurons were missing, and most of the major dorsal thalamic nuclei were not identifiable. However, the ventral thalamus was essentially unaffected, although the dorsal thalamic defect leads to rostral displacement of portions of the ventral thalamus. Analysis of younger embryos showed that epithalamic and dorsal thalamic neurons were not produced at early stages of development, whereas ventral thalamic neurons were still produced. These defects were accompanied by improper formation of the boundary between dorsal and ventral thalamus, the zona limitans interthalamica (ZLI). Furthermore, the expression of an early marker of posterior forebrain development that marks the compartment from the midbrain-hindbrain junction to the ZLI (including the future dorsal thalamus, pretectum, and midbrain) was disrupted, supporting the idea that diencephalic development is abnormal from very early in embryogenesis. This study provides compelling in vivo evidence that thalamic development requires normal activity of the LRP6-mediated canonical Wnt signaling pathway.